Interaction of calcium phosphate and CaO (CaCO3) while their disposing on the titanium surface under gas detonation conditions - Zatovsky, I.V.; Nikolenko, I.O.; Slobodyanik, M.S.; Klyui, N.I.; Temchenko, V.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The gas detonation deposition of calcium hydrogen phosphate and CaO (CaCO3) has been conducted on the titanium surface. Powder XRD and IR-spectroscopy have been performed for the composition analysis of the obtained coating. It has been shown that, using such technology, the composite compounds can be obtained, by basing on Ca3(PO4)2, Ca10(PO4)6O, Ca5(PO4)3OH precursors. Such synthetic route demonstrates new possibilities for improving the technologies of obtaining metallic implants for medical use.